2005
DOI: 10.14411/fp.2005.022
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrosporidial activity of (fluoro)quinolones in vitro and in vivo

Abstract: Abstract. Microsporidia are a cause of emerging and opportunistic infections in humans and animals. Although two drugs are currently being used to treat microsporidiosis, concerns exist that albendazole is only selective for inhibiting some species of microsporidia that infect mammals, and fumagillin appears to have been found to be toxic. During a limited sequence survey of the Vittaforma corneae (syn. Nosema corneum Shadduck, Meccoli, Davis et Font, 1990) genome, a partial gene encoding for the ParC topoisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
0
20
0
2
Order By: Relevance
“…This approach was used to screen a variety of drugs for their therapeutic potential and to identify albendazole and fumagilin as effective at inhibiting the growth of E. cuniculi in vitro but at the same time causing little harm to the human cells, which in this case were MRC5 (Beauvis et al 1994). Similar systems have been used to evaluate the antimicrosporidial activity of other classes of compounds, including fluoroquinolones (Didier et al 2005; Didier et al 2006). Although animals ultimately will have to be used to test the efficacy of therapeutics, the advantage of the in vitro approach is in providing preliminary screens of effectiveness rapidly and inexpensively.…”
Section: Culturing Microsporidia Of Human Diseasesmentioning
confidence: 99%
“…This approach was used to screen a variety of drugs for their therapeutic potential and to identify albendazole and fumagilin as effective at inhibiting the growth of E. cuniculi in vitro but at the same time causing little harm to the human cells, which in this case were MRC5 (Beauvis et al 1994). Similar systems have been used to evaluate the antimicrosporidial activity of other classes of compounds, including fluoroquinolones (Didier et al 2005; Didier et al 2006). Although animals ultimately will have to be used to test the efficacy of therapeutics, the advantage of the in vitro approach is in providing preliminary screens of effectiveness rapidly and inexpensively.…”
Section: Culturing Microsporidia Of Human Diseasesmentioning
confidence: 99%
“…and E. bieneusi in vitro (Bacchi and Weiss, 2004 ). The antimicrosporidial activity of various fluoroquinolones derivatives such as norfloxacin ( 4 ) and ofloxacin ( 5 ) is more than gatifloxacin ( 6 ), lomefloxacin ( 7 ), moxifloxacin ( 8 ), and nalidixic acid ( 9 ) and can be the effective option of chemotherapy (Didier et al, 2005 ). It was observed that TNP-470 ( 10 ), ovalicin ( 11 ) and its derivatives inhibited E. intestinalis replication by more than 70% in vitro which indicates that these compounds can be used as medication for this infection (Didier et al, 2006 ).…”
Section: Microsporidiamentioning
confidence: 99%
“…In addition, nalidixic acid, norfloxacin, ofloxacin, moxifloxacin, gatifloxacin, lomefloxacin, and some more fluoroquinolones inhibited growth of the microsporidia Encephalitozoon intestinalis and Vittaforma corneae to 50 % at concentrations ranging from 0.9 to 98.4 μM [112]. Furthermore, ciprofloxacin caused a 50 % growth inhibition of Babesia microti, B. bigemina, B. caballi, B. equi, and B. bovis at concentrations of 2.5 to 15.8 μM [113].…”
Section: Antiparasitic Activities Of Fluoroquinolonesmentioning
confidence: 98%
“…Nalidixic acid and several fluoroquinolones like ciprofloxacin, norfloxacin, enoxacin, ofloxacin, fleroxacin, clinafloxacin, pefloxacin, and sparfloxacin exerted an antitrypanosomal in vitro and in vivo effect at micromolar concentrations [38,[106][107][108][109][110][111][112][113][114][115][116].…”
Section: Antiparasitic Activities Of Fluoroquinolonesmentioning
confidence: 99%